Evaluation of antibacterial activity of branched quaternary ammonium grafted green polymers. (June 2017) - Belkhir, Kedafi; Lacroix, Monique; Jamshidian, Majid; Salmieri, Stéphane; Jegat, Corinne; Taha, Mohamed
Graphical abstract: Highlights: New quaternary ammonium (QA) functionalized polymers (QAFPs) are highly antibacterial. The antibacterial activity of the QA (meth)acrylic monomers is preserved when they are grafted on polymers. The inhibition of the bacterial growth, as well as the bactericidal activity, depend on the QA content in the film. The action of the films bearing QA groups occurs according to a contact-killing mechanism. Both Gram-positive and Gram-negative bacteria are subjects of the antibacterial activity of the QAFPs. Abstract: This study describes the antibacterial activity evaluation of film-shaped polymers based on biodegradable chains of polylactic acid (PLA), polycaprolactone (PCL) and polyhydroxybutyrate (PHB) in branched structures with quaternary ammonium pendant groups. The materials were tested against both Gram-negative ( Escherichia coli and Salmonella Typhimurium) and Gram-positive ( Listeria monocytogenes ) bacteria. Minimal inhibitory and maximal tolerated concentrations of the quaternary ammonium monomers were first determined. Films of pure quaternary ammonium functionalized polymers (QAFPs) and of blends of QAFPs with commercial matrices were studied to determine their inhibition effects and their bactericidal activity. A high antibacterial activity was found, up to 5.6 log, 4.4 log, and 4.2 log CFU.mL-1 reduction for respectively Escherichia coli (Salmonella Typhimurium and Listeria monocytogenes after only one hour of bactericidal tests, 6.7 log, 5.2 log and 4.9 log CFU.mL −1 reduction was observed for the respectively cited bacteria after 24 h, making these materials potentially applicable in many fields.